Explaining tort and crime : legal development across laws and legal systems, 1850-2020 / Matthew Dyson. - Dyson, Matthew, 1982- (Cambridge University Press, 2022)
Tracing almost 200 years of history, Explaining Tort and Crime explains the development of tort law and criminal law in England compared with other legal systems. Referencing legal systems from around the globe, it uses innovative comparative and historical methods to identify patterns of legal development, to investigate the English law of fault doctrine across tort and crime, and to chart and explain three procedural interfaces: criminal powers to compensate, timing rules to control parallel actions, and convictions as evidence in later civil cases. Matthew Dyson draws on decades of research to offer an analysis of the field, examining patterns of legal development, visible as motifs in the law of many legal systems.